2010
DOI: 10.4141/cjas09084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corn-, wheat- or triticale dry distillers’ grains with solubles on in vitro fermentation, growth performance and carcass traits of lambs

Abstract: . 2010. Effects of corn-, wheator triticale dry distillers' grains with solubles on in vitro fermentation, growth performance and carcass traits of lambs. Can. J. Anim. Sci. 90: 99Á108. The objective of this study was to determine the effect of replacing a mixture of canola meal and barley grain with corn-, wheat-or triticale dry distillers' grains with solubles (DDGS) at 20% of dietary dry matter (DM) on in vitro ruminal fermentation in bovine ruminal fluid and on growth performance and carcass characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 45 publications
1
32
4
1
Order By: Relevance
“…In agreement with this study reported here, Abdelrahim et al (2014) reported that DM intake was not affected when lambs were fed DDGS at 0, 127 and 254 g/kg DM and DM intake was not affected when beef cattle were fed a concentrate diet that contained DDGS at 230 g/kg DM (Beliveau and McKinnon 2008). On the other hand, other studies have found that nutrient intakes were either improved or not affected when growing lambs or beef steers were fed DDGS fed at variable concentrations (Huls et al 2006;Buckner et al 2008;Mckeown et al 2010;Felix et al 2012).…”
Section: Discussionmentioning
confidence: 58%
“…In agreement with this study reported here, Abdelrahim et al (2014) reported that DM intake was not affected when lambs were fed DDGS at 0, 127 and 254 g/kg DM and DM intake was not affected when beef cattle were fed a concentrate diet that contained DDGS at 230 g/kg DM (Beliveau and McKinnon 2008). On the other hand, other studies have found that nutrient intakes were either improved or not affected when growing lambs or beef steers were fed DDGS fed at variable concentrations (Huls et al 2006;Buckner et al 2008;Mckeown et al 2010;Felix et al 2012).…”
Section: Discussionmentioning
confidence: 58%
“…The literature reports that DDGS can be used in animal feed, because it has protein characteristics, which can replace soybean meal, in order to reduce the cost of animal feed (SPIEHS et al, 2002;McKEOWN et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The DDGS tended to increase the proportion of butyrate in the rumen although the total concentrations of volatile fatty acids were higher on the diet without DDGS. The feed intake of lambs in response to DDGS inclusion does not appear to depend on the source grain of the DDGS, with similar effects being observed on diets containing maize, barley or wheat DDGS at 20 % of a grower diet (McKeown et al, 2010). However, feed efficiency was poorer on the wheat DDGS than on the maize DDGS, due to greater production of ruminal ammonia and lower digestibility of the former.…”
Section: Ruminant Animal Productionmentioning
confidence: 73%